HUBUNGAN ANTARA AKTIVITAS FISIK DENGAN TINGKAT KESEIMBANGAN PADA LANSIA DI MAJELIS TAKLIM HUSNUL KHOTIMAH TAHUN 2025 - Yani Christina; Sukma Sahreny; Silvia Haryati Angela Putri (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: The elderly experience physiological decline as they age, affecting muscle strength, sensory systems, and postural stability, which in turn influences body balance. Optimal physical activity is known to improve dynamic balance and reduce the risk of falling. This study aims to determine the relationship between physical activity and balance level in the elderly at Majelis Taklim Husnul Khotimah in 2025. Methods: This study used an observational analytic method with a cross-sectional approach. The sample consisted of 50 elderly individuals selected using total sampling. Physical activity was measured using the Physical Activity Scale for the Elderly (PASE) questionnaire, and dynamic balance was assessed using the Timed Up and Go Test (TUGT). Data were analyzed using the Chi-Square test. Results: A total of 42.0% of elderly individuals had a low level of physical activity, and 46.0% had impaired balance. The chi-square test results showed a significance value (p-value) of 0.001. Conclusion: There is a significant relationship between physical activity and balance level among the elderly at Majelis Taklim Husnul Khotimah in 2025. Elderly with low levels of physical activity tend to have impaired balance. Keywords: Physical Activity, Balance, Elderly